Application of Various Techniques to Gain Insights Into the Complex Urinary Tract Microbial Communities of Renal Transplant Recipients. Issue 2 (6th January 2023) - Sathiananthamoorthy, Sanchutha; Florman, Katia; Richard, Damien; Cheng, Ka Kei; Torri, Vittoria; McCaig, Fiona; Harber, Mark; Rohn, Jennifer L.
Abstract : Background: Urinary tract infections (UTIs) are prevalent in renal transplant (RTX ) recipients and associated with worse outcomes. Early detection by sensitive diagnostic tests and appropriate treatment strategies in this cohort is therefore crucial, but evidence has shown that current methods may miss genuine infections. Research has shed light on the urinary tract microbial ecology of healthy individuals and nontransplant patients with UTI, but information on the RTx cohort is scant. We conducted a cross-sectional study to (i) compare the gold standard diagnostic culture with alternative techniques and (ii) characterize RTx patient urinary microbial communities. Methods: Midstream urine specimens were collected from 51 RTx patients attending a renal transplant clinic and 27 asymptomatic controls. Urinary microscopy, dipstick, and routine culture were performed. To improve sensitivity of microbial detection, we cultured the urinary cell sediment and performed 16S rRNA gene sequencing on urine. Uroplakin-positive urothelial cells shed in urine were analyzed by immunofluorescence staining for any bacterial association. Results: Sediment culture and 16S rRNA sequencing confirmed detection deficiencies of diagnostic culture and revealed differences in the urobiomes of RTx patients and controls. Specifically, Gardnerella, Escherichia, and Lactobacillus were most abundant in patients, whereas Lactobacillus, Streptococcus, and Gardnerella were most abundant in controls. The application of both culture and sequencing provided a more nuanced view of the urinary microbial communities. Conclusions: This study provides insight into the potential problems of diagnostic culture within RTx patients and sheds light on their urinary microbial inhabitants. Further work may identify key microbial signatures and facilitate the development of better tools for UTI detection within this cohort, which could allow targeted intervention before an infection leads to serious consequences. http://links.lww.com/TXD/A479 Abstract :